Biological parameters of soybean looper in cotton cultivars with the Cry1Ac and Cry1F proteins - Viana, Daniela de Lima; Crosariol Netto, Jacob; Aguirre-Gil, Oniel Jeremías; Busoli, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effects of transgenic cotton cultivars expressing the Cry1Ac and Cry1F proteins, on the biological parameters of soybean looper (Chrysodeixis includens). Neonate larvae were fed during the entire larval phase with leaves from transgenic cultivars and their conventional isolines. In the Nuopal (Bollgard I) cultivar (Cry1Ac), 62% of larvae survived and became normal pupae. The FM 975 (WideStrike) cultivar (Cry1Ac and Cry1F) is lethal to first‑instar larvae, with 100% mortality.